Sensitivity to near-future CO2 conditions in marine crabs depends on their compensatory capacities for salinity change. Issue 1 (December 2018) - Whiteley, Nia; Suckling, Coleen; Ciotti, Benjamin; Brown, James; McCarthy, Ian; Gimenez, Luis; Hauton, Chris
Abstract Marine crabs inhabit shallow coastal/estuarine habitats particularly sensitive to climate change, and yet we know very little about the diversity of their responses to environmental change. We report the effects of a rarely studied, but increasingly prevalent, combination of environmental factors, that of near-futurep CO2 ( 1000 µatm) and a physiologically relevant 20% reduction in salinity. We focused on two crab species with differing abilities to cope with natural salinity change, and revealed via physiological and molecular studies that salinity had an overriding effect on ion exchange in the osmoregulating shore crab, Carcinus maenas . This species was unaffected by elevated CO2, and was able to hyper-osmoregulate and maintain haemolymph pH homeostasis for at least one year. By contrast, the commercially important edible crab, Cancer pagurus, an osmoconformer, had limited ion-transporting capacities, which were unresponsive to dilute seawater. Elevated CO2 disrupted haemolymph pH homeostasis, but there was some respite in dilute seawater due to a salinity-induced metabolic alkalosis (increase in HCO3 − at constantp CO2 ). Ultimately, Cancer pagurus was poorly equipped to compensate for change, and exposures were limited to 9 months. Failure to understand the full spectrum of species-related vulnerabilities could lead to erroneous predictions of the impacts of a changing marine climate.